PRAKTEK AKUNTANSI DALAM RUMAH TANGGA - Harun Alrasyid; Poppy Ruddin; Sultan Sultan (Institut Teknologi dan Bisnis Swadharma, 2025)
This study aims to explore how individuals apply household accounting practices and how these experiences shape families' financial management. Using a qualitative phenomenological approach, the research investigates participants' subjective experiences in recording, organizing, and analyzing their household finances. Data were collected through semi-structured in-depth interviews with individuals or couples responsible for managing family finances, complemented by observations and the analysis of financial documents. The findings reveal that household accounting practices offer significant benefits in enhancing financial awareness, controlling expenses, and supporting the achievement of both short-term and long-term financial goals. Despite several challenges, including limited accounting knowledge, consumerist habits, and differing financial perspectives between spouses, participants demonstrated the ability to adapt by relying on values such as responsibility, simplicity, and religious teachings. This study concludes that household accounting is not merely a technical activity but also a meaningful process that fosters financial awareness and family self-reliance. These insights are expected to serve as a foundation for developing more contextual and practical financial education for households.Penelitian ini bertujuan untuk memahami bagaimana individu menerapkan praktik akuntansi dalam rumah tangga dan bagaimana pengalaman tersebut memengaruhi pengelolaan keuangan keluarga. Menggunakan pendekatan kualitatif fenomenologi, penelitian ini menggali pengalaman subjektif partisipan dalam mencatat, mengatur, dan menganalisis keuangan rumah tangga mereka. Data dikumpulkan melalui wawancara mendalam semi-terstruktur kepada individu atau pasangan yang bertanggung jawab atas keuangan keluarga, dilengkapi dengan observasi dan analisis dokumen pengeluaran. Hasil penelitian menunjukkan bahwa praktik akuntansi rumah tangga memberikan manfaat nyata dalam meningkatkan kesadaran finansial, membantu pengendalian pengeluaran, serta mendukung pencapaian tujuan keuangan jangka pendek dan panjang. Meskipun ditemukan beberapa kendala seperti minimnya pengetahuan akuntansi, kebiasaan konsumtif, dan perbedaan persepsi antar pasangan, partisipan mampu mengembangkan strategi adaptif berbasis nilai-nilai tanggung jawab, kesederhanaan, dan ajaran agama. Penelitian ini menyimpulkan bahwa akuntansi rumah tangga bukan hanya aktivitas teknis, tetapi juga bagian dari proses pembentukan kesadaran dan kemandirian finansial keluarga. Temuan ini diharapkan dapat menjadi dasar bagi pengembangan edukasi keuangan rumah tangga yang lebih relevan dan membumi.